Neoliberalism and the global imbalances: The neo-Gramscian approach - Naphon Phumma (The University of Utah, Department of Economics, 2014)
This paper argues that the current episode of global imbalances is caused by the rise of neoliberalism. The paper employs the neo-Gramscian approach to understand the emergence and expansion of neoliberalism. The global imbalances have been the economic consequences of the rise of neoliberalism as a new world order. As no significant counter-hegemonic challenge is likely to occur, the neoliberal world order is likely to remain intact in the near future. To the extent that the neoliberal world order prevents an effective rebalancing of the global imbalances, the current episode of global imbalances may end up with a hard-landing of the global economy.
Keywords: B51; F01; F50; P16; 330; Global Imbalances; Neoliberalism; Neo-Gramscian